Digital Service Experience dan Loyalitas Pelanggan: Studi Perbandingan Bank CIMB Niaga dan Hotel Bintang Empat - Widi Maulana Kurnia Aji; Enik Rahayu (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This article aims to describe and compare digital service experiences and their role in shaping customer loyalty in CIMB Niaga Bank and four-star hotels in Semarang City. The study focuses on how digital service experience patterns are perceived by customers and how these experiences influence loyalty across two service industries with distinct service characteristics.  Data were collected through in-depth interviews with CIMB Niaga customers and guests of four-star hotels, supported by digital service documentation and customer reviews, and analyzed qualitatively using thematic analysis and cross-case comparison. The findings indicate that in the banking industry, digital service experience is centered on security, system reliability, and service consistency as the foundation for building trust and long-term customer loyalty. In contrast, the hospitality industry emphasizes ease of access to information, clarity of digital communication, and service responsiveness, which influence revisit intention and customer recommendations. This study concludes that digital service experience plays a strategic role in shaping customer loyalty; however, its management must be aligned with the characteristics of each service industry.